2009
DOI: 10.1038/gt.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival gene delivery of the transcription factor GA-binding protein delays corneal neovascularization in a mouse model

Abstract: Corneal neovascularization can reduce visual acuity. GAbinding protein (GABP) is a transcription factor that regulates the expression of target genes including vascular endothelial growth factor (VEGF) and roundabout4 (Robo4), which participate in pathologic angiogenesis. We assessed whether intraocular injection of the GABP gene affects the growth of new corneal blood vessels in a mouse ocular neovascularization model. Transfection of human GABPa and GABPb gene (GABPa/b) into human conjunctival epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…In vivo experiments were done in HSV infected animals to determine if the lentiviral vector expressing Slit2 shRNAs had any effect on the extent of angiogenesis. The subconjunctival delivery (25) of lentiviruses encoding Slit2 shRNAs was started from day 1 post HSV infection with additional administrations on alternate days (fig 3C). Corneas collected at day 9 revealed diminished Slit2 mRNA and protein compared to controls (fig 3D&E) suggesting a reduction in Slit2 mRNA and protein in vivo after lentiviral Slit2 shRNA administrations.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments were done in HSV infected animals to determine if the lentiviral vector expressing Slit2 shRNAs had any effect on the extent of angiogenesis. The subconjunctival delivery (25) of lentiviruses encoding Slit2 shRNAs was started from day 1 post HSV infection with additional administrations on alternate days (fig 3C). Corneas collected at day 9 revealed diminished Slit2 mRNA and protein compared to controls (fig 3D&E) suggesting a reduction in Slit2 mRNA and protein in vivo after lentiviral Slit2 shRNA administrations.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest a homoeostatic role for GABP in promoting quiescence of the vascular wall. A recent report by Yoon et al [38] found that intraocular injection of the GABP gene delayed corneal neovascularization in a mouse model, providing the first direct evidence for a role of GABP in adult angiogenesis in vivo.…”
Section: Gabp (Ga-binding Protein)mentioning
confidence: 96%
“…Other gene transfer studies have assessed the utility of CD36 (Mwaikambo et al, 2006), pigment epithelium derived factor (Kuo et al, 2009), and GA binding protein (Yoon et al, 2009) among other approaches to treating CNV. Future experiments may include vector mediated delivery of inhibitors of angiogenesis derived from basement membrane such as neostatin, restin, arresten, canstatin, and tumstatin (Ellenberg et al, 2010).…”
Section: Gene Therapy Updates In Various Corneal Disordersmentioning
confidence: 99%